Relation of Lymphocyte Subsets and Cytokines in Different Grades of Alcoholic Cirrhosis - Archana Chirag Buch; Amardeep Patil; Niladri Haldar; Banyameen Iqbal; Dakshayani Pandit; Arjun lal Kakrani; Sunita Bamanikar; Harsh Kumar (Journal of Clinical and Diagnostic Research, 2019)
Introduction: The pathogenesis of Alcoholic Liver Disease (ALD) shows immune dysregulation with decreasing lymphocyte subsets and increasing CD4/CD8 ratio. T lymphocyte activation leads to secretion of cytokines like Tumour Necrosis Factor-a (TNF-a) and interleukins causing inflammation and fibrosis. Aim: To correlate lymphocyte subsets and TNF-a and Interleukin 6 (IL-6) in different grades of alcoholic cirrhosis. Materials and Methods: This was a prospective, crosssectional study carried out over a period of two years at a tertiary care hospital and research centre in Western Maharashtra. The study cohort consisted of 51 patients diagnosed clinically as alcoholic cirrhosis. They were classified into grades A, B and C by Child-Pugh’s score. Lymphocyte subsets were determined by flow cytometry. T lymphocytes were identified (CD3+), and further subdivided into CD4+and CD8+cells. TNF-a and IL-6 were measured by ELISA. All parameters were measured using one-way Analysis of Variance (ANOVA test). Results: There was insignificant change in the total number of lymphocytes with different grades of cirrhosis. T lymphocytes and CD4+cells showed increase in count (885.38±464.19/ mm3 to 1002.81±338.52/mm3 ) and (489.63±248.23/mm3 to 689.05±263.08/mm3 ) respectively, with corresponding decrease in CD8 count (364±230.37 to 3440.38±165.91). There was also an increase in CD4/CD8 ratio (1.48 to 2.18) along with raised TNF-a (25.16±18.45 to 30.15±36.37) and IL-6 (58.27±50.52 to 175.38±241.85) with increasing grades of cirrhosis. Conclusion: Alcoholic cirrhosis is a complex entity caused due to interaction between various components of immune systems and elaboration of cytokines. We found increase in T lymphocytes and CD4+cells along with increase in cytokines TNF-a and IL-6 with increase in grades of cirrhosis.